Caracterização morfofisiológica de sementes e crescimento inicial de mudas de pau-rainha (Centrolobium paraense Tul. - Fabaceae) em Boa Vista - Roraima - Schwengber, Luís Augusto Melo (2015)
Centrolobium paraense has a straight stem which makes its wood appreciated by the local population, usually being used in housing construction and making handmade furniture. The objective of this study was to characterize the seed germination morphophisiology and to assess the early growth of canary wood (Centrolobium paraense Tul.) seedlings in Boa Vista, Roraima. The seeds came from fruits (samaras) collected from trees located at Água Boa and Taiano in April/2013 and March/2014, in Boa Vista, Roraima. The parameters assessed were seed integument colour, water absortion and vigor trough the electrical conductivity test, emergence of seedlings and seedling emergence speed. Concerning the study on shading and mineral fertilization of the seedlings six arrangements of fertilization and two shade environments were tested, in which the parameters assessed were shoot height, stem diameter at ground level, the radicular, shoot and total dry masses and Dickson’s index. C. paraense from Água Boa and Taiano place from 2013 and 2014 show seeds with integuments with three different colours. The water-absorption curve from seeds of C. paraense with integuments of different colours from both Água Boa and Taiano from both years of 3013 and 2014 showed differentiated paterns of embebition. Light-brown seeds of C. paraense from both Água Boa and Taiano from both years of 3013 and 2014 showed higher physiological quality compared to others concerning vigor tests. Use of double layer of shade screen and addition of nutritive solution and of inoculum (ERR 326) provides improvements in initial growth and quality of C. paraense seedlings.